Data-Based Policy as a solution to overcome illegal mining of Mount Botak, Buru Regency, Mollucas Province for sustainable development - Martanto, Dwiana; Nasihuddin, Abdul Aziz (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Gold mining in Mount Botak, Buru Regency, Mollucas Province is processed traditionally so that it produces waste containing heavy metals that are harmful to human health and cause environmental damage. Although the government has taken various control measures in the form of judicial operations, they have not been effective in stopping illegal mining activities, even indigenous peoples in the name of customary rights have urged the government to manage them professionally for economic reasons. The Buru Regent is challenged to make legal policies that respond to the demands of the community while at the same time paying attention to environmental sustainability. This study aims to find the ideal policy concept for overcoming illegal mining that supports environmental sustainability. To achieve this goal, doctrinal legal research is used based on a conceptual approach, with a positivist paradigm, and relies on normative juridical research, and deductive analysis. The results of the study show that a data-based policy model that is supported by science becomes a reliable policy and supports sustainable environmental development